Development of vocational marine schools in Indonesia as a strategy for rediscovering Indonesia's maritime potential - Irfan Teguh Prima; M. Hazmi Ash-Shidqi; Opi Aristya (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
As a nation gifted with approximately 5.8 million km sq of water areas and abundant marine biodiversity, Indonesia is expected to be able to prosper its citizen by utilizing its potential maritime sector. Unfortunately, maritime sector in Indonesia is still neglected. Vocational school of fisheries and marines is a breakthrough designed to improve the utilization of maritime sector. This paper attempts to provide analysis of factors impeding the development of marine vocational schools in Indonesia and possible solutions for the impediments. The research was conducted using literature review and direct observation at a marine vocational school in Tuban, East Java. Based on the observation, factors that impede the development of marine vocational schools are related to the curriculum design and capital invested. The solutions proposed consist of emphasizing technical skills in curriculum design, improving capital investment of public sector, and maintaining partnership with state-owned enterprises in maritime sectors.
Keywords: 650; Fisheries; Marine; Vocational School